2006
DOI: 10.1097/01.opx.0000230270.39804.54
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Refractive Error: Comparison of Autorefractor and Focometer

Abstract: This study highlighted the focometer's restricted power range, inaccuracy of astigmatism and axis determination, and dependence on subject understanding and compliance. Therefore, in most clinical settings, the focometer would not be adequate for quantifying refractive error, but the focometer spherical equivalent was within acceptable limits of the autorefractor, and the visual acuity with lenses determined by the focometer indicates its potential usefulness in public health settings, especially where only sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
4
2
Order By: Relevance
“…These findings are different from the findings of Du Toit et al 15 in Australia where autorefractor showed that 63% of the study population were myopic, 36% were hypermetropic and 91% had astigmatism while only 32% had astigmatism with the focometer. This variation may be related to differences in the definitions of refractive error used, differences in age group and ethnicity of the study population.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…These findings are different from the findings of Du Toit et al 15 in Australia where autorefractor showed that 63% of the study population were myopic, 36% were hypermetropic and 91% had astigmatism while only 32% had astigmatism with the focometer. This variation may be related to differences in the definitions of refractive error used, differences in age group and ethnicity of the study population.…”
Section: Discussioncontrasting
confidence: 56%
“…This was low compared to the findings by Du Toit et al 15 where 99% of the population studied had refractive error using the autorefractor. This may be due to the differences in definitions of the refractive errors used in their study compared with this study.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations